Reshaping performance management for sustainable development - Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio; Allegrini, Veronica (Studies in public and non-profit governance ;, 2023)
Public sector organizations play a crucial role in addressing the challenge of sustainability and sustainable development. They adopt policies and strategies, provide public services, mobilize and distribute financial resources, and are responsible for monitoring, evaluating, and reporting strategy implementation and goal achievement. The non-profit sector also supports sustainable development alone or through partnerships with the public sector. Including sustainability goals and practices in the strategy and management of public and non-profit organizations considering their characteristics is a nodal point. To this aim designing effective performance management systems integrating sustainability aspects is crucial. Reshaping Performance Management for Sustainable Development explores how sustainability can be integrated into the management of public and non-profit organizations through performance management systems. The Studies in Public and Non-Profit Governance (SPNPG) series focuses on the "micro" level of governance in public and non-profit sector, investigating governance systems, mechanisms and roles at an organizational level.